2022
DOI: 10.3390/pathogens11020131
|View full text |Cite
|
Sign up to set email alerts
|

First Isolation of Virulent Tenacibaculum maritimum Isolates from Diseased Orbicular Batfish (Platax orbicularis) Farmed in Tahiti Island

Abstract: The orbicular batfish (Platax orbicularis), also called ‘Paraha peue’ in Tahitian, is the most important marine fish species reared in French Polynesia. Sudden and widespread outbreaks of severe ‘white-patch disease’ have occurred since 2011 in batfish farms one to three weeks after the transfer of juveniles from bio-secured hatcheries to lagoon cages. With cumulative mortality ranging from 20 to 90%, the sustainability of aquaculture of this species is severely threatened. In this study, we report for the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Moreover, scanning electron microscopy revealed the presence of filamentous, Gram-negative bacteria in the dermis layer and over the scales. Other research in a P. orbiculares specimen associated the intensity of ulcerative skin lesions with the number and area of whitish patches caused by T. maritimum (Lopez et al, 2022b). The respective histopathological view thereof for affected skin showed severe degeneration in both the dermis and epidermis layers with an aggregation of filamentous bacteria and leukocyte infiltration.…”
Section: Presumptive and Confirmative Diagnostic Procedures For Tenac...mentioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, scanning electron microscopy revealed the presence of filamentous, Gram-negative bacteria in the dermis layer and over the scales. Other research in a P. orbiculares specimen associated the intensity of ulcerative skin lesions with the number and area of whitish patches caused by T. maritimum (Lopez et al, 2022b). The respective histopathological view thereof for affected skin showed severe degeneration in both the dermis and epidermis layers with an aggregation of filamentous bacteria and leukocyte infiltration.…”
Section: Presumptive and Confirmative Diagnostic Procedures For Tenac...mentioning
confidence: 89%
“…Tenacibaculum maritimum has even extended beyond foodoriented fish to some valuable ornamental fish, including the Picasso triggerfish, black damselfish, and broomtail wrasse in Egypt (Abd El-Galil and Hashiem, 2011;Abd El-Galil and Hashem, 2012a;Haridy et al, 2015). In French Polynesia, this bacterium has been described as the cause of massive mortalities (up to 90%) among the tropical orbicular batfish (Platax orbicularis) (Lopez et al, 2022b). Despite significant efforts to remain free-of T. maritimum infections in Chile, which is the second largest producer of salmon after Norway, outbreaks of T. maritimum have been reported in farmed Atlantic salmon (Apablaza et al, 2017) and rainbow trout (Valdes et al, 2021), and outbreaks have likewise been reported in Canada among Sockeye salmon (Oncorhynchus nerka) (Nekouei et al, 2018).…”
Section: Geographical Distribution and Host Susceptibilitymentioning
confidence: 99%
“…It has originally been isolated in 1977 in Japan during mortality events on marine red seabream ( Pagrus major ) and black sea bream ( Acanthopagrus schlegelii ) (Masumura & Wakabayashi, 1977; Wakabayashi et al., 1984). Since then, it has been retrieved from a large variety of marine fish species worldwide including: Atlantic salmon ( Salmo salar ) in Australia (van Gelderen, 2007) and in Chile (Apablaza et al., 2017), rainbow trout ( Oncorhynchus mykiss ) in Australia (van Gelderen, 2007) and in Chile (Valdes et al., 2021), Chinook salmon ( Oncorhynchus tshawytscha ) in Canada (Ostland et al., 1999), turbot ( Scophthalmus maximus ), sole ( Solea solea ) and blackspot seabream ( Pagellus bogaraveo ) in Spain (Castro et al., 2007), batfish ( Platax orbicularis ) in French Polynesia (Lopez et al., 2022) and sea bass ( Dicentrarchus labrax ) and seabream ( Sparus aurata ) in Europe (Muniesa et al., 2020). Fish often display gross external lesions including eroded mouth, skin ulcers or necrosis, frayed fins and tail rot (Avendaño‐Herrera et al., 2006; Nowlan et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…in Canada (Ostland et al, 1999), turbot (Scophthalmus maximus), sole (Solea solea) and blackspot seabream (Pagellus bogaraveo) in Spain (Castro et al, 2007), batfish (Platax orbicularis) in French Polynesia (Lopez et al, 2022) and sea bass (Dicentrarchus labrax) and seabream (Sparus aurata) in Europe (Muniesa et al, 2020). Fish often display gross external lesions including eroded mouth, skin ulcers or necrosis, frayed fins and tail rot (Avendaño-Herrera et al, 2006;Nowlan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%